THE GROWING ROLE AND IMPORTANCE OF ECONOMIC JOURNALISM IN SOCIETY (International journal of artificial intelligence, 2026)
This article examines the key characteristics of business (economic) journalism, which is developing rapidly in the modern era, as well as its types and the increasing significance of this field in contemporary society. The study analyzes the factors influencing the development of business journalism, previous and current perspectives on this field, and the areas most frequently used in commerce and marketing. In addition, the article highlights the positive impact of business journalism on the image, brand recognition, and profitability of companies and corporations.